2017
DOI: 10.1016/j.bbamcr.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microRNA expression in vascular smooth muscle by MRTF-A and actin polymerization

Abstract: The dynamic properties of the actin cytoskeleton in smooth muscle cells play an important role in a number of cardiovascular disease states. The state of actin does not only mediate mechanical stability and contractile function but can also regulate gene expression via myocardin related transcription factors (MRTFs). These transcriptional co-activators regulate genes encoding contractile and cytoskeletal proteins in smooth muscle. Regulation of small noncoding microRNAs (miRNAs) by actin polymerization may med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 84 publications
(89 reference statements)
0
15
0
Order By: Relevance
“…Findings in human samples then largely corroborate the hypothesis that the cluster is downregulated in disease, consistent in aortic aneurysm tissue versus control, and in the PBMCs of hypertensive patients ( Elia et al, 2009 ; Kontaraki et al, 2014 ). It has been demonstrated that the process of actin depolymerisation in mild aortic dilation leads to downregulation of miR-143/145 regulated by myocardin-related transcription factors (MRTFs) ( Alajbegovic et al, 2017 ). However, another level of complexity is suggested by conflicting evidence in apparent upregulation in carotid artery plaques of patients with stroke ( Cipollone et al, 2011 ), and similarly higher expression in the carotid plaques of patients with hypertension ( Santovito et al, 2013 ), and pulmonary artery SMCs of patients with pulmonary hypertension ( Caruso et al, 2012 ; Deng et al, 2015 ).…”
Section: Mirnasmentioning
confidence: 99%
“…Findings in human samples then largely corroborate the hypothesis that the cluster is downregulated in disease, consistent in aortic aneurysm tissue versus control, and in the PBMCs of hypertensive patients ( Elia et al, 2009 ; Kontaraki et al, 2014 ). It has been demonstrated that the process of actin depolymerisation in mild aortic dilation leads to downregulation of miR-143/145 regulated by myocardin-related transcription factors (MRTFs) ( Alajbegovic et al, 2017 ). However, another level of complexity is suggested by conflicting evidence in apparent upregulation in carotid artery plaques of patients with stroke ( Cipollone et al, 2011 ), and similarly higher expression in the carotid plaques of patients with hypertension ( Santovito et al, 2013 ), and pulmonary artery SMCs of patients with pulmonary hypertension ( Caruso et al, 2012 ; Deng et al, 2015 ).…”
Section: Mirnasmentioning
confidence: 99%
“…As a consequence, an increase in G-actin may alter the phenotype of SMCs, from a highly contractile phenotype to a more proliferative phenotype. In a recent study, we have demonstrated that polymerization of actin filaments, and MRTF-dependent gene expression, is reduced in mildly dilated aortas from patients with stenotic tricuspid aortic valve (TAV) or BAV (Alajbegovic et al, 2016 ). This result suggests that altered actin polymerization may be an early event in the development of ascending aortic aneurysm and that the effect is not specific for BAV-associated disease.…”
Section: The Role Of Actin Polymerization In the Development Of Artermentioning
confidence: 99%
“…Although miR-29 appears to be particularly promising for therapeutic intervention, additional miRNAs have been demonstrated to be dysregulated in aortic aneurysms, including miR-21 (Maegdefessel et al, 2012a ), miR-26 (Leeper et al, 2011 ), and the miR-143/145 cluster (Elia et al, 2009 ). In a recent study, we demonstrated that a group of smooth muscle miRNAs, including miR-143/145, miR-1, miR-378a, and miR-22, are regulated by actin dynamics via the actin sensitive transcription factor MRTF-A (Alajbegovic et al, 2016 ). With the exception of miR-22, these miRNAs were found to be highly enriched in muscle-containing tissues and downregulated in phenotypically modified SMCs.…”
Section: Role Of Micrornas In Aneurysm Developmentmentioning
confidence: 99%
See 2 more Smart Citations